2009
DOI: 10.1007/s10340-009-0270-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential for biological control of potato field pests in Ardabil, Iran: functional responses of Orius niger (Wolf.) and O. minutus (L.) (Hemiptera: Anthocoridae)

Abstract: The two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae), and the onion thrips, Thrips tabaci Lind. (Thysanoptera: Thripidae), are significant field pests of potato in the Ardabil region of Iran. Orius niger (Wolf.) and O. minutus (L.) (Hemiptera: Anthocoridae) are locally the predominant natural enemies of these pests. This study compared the functional responses of O. niger and O. minutus to female mites and second instar thrips larvae across a range of prey densities (5, 10, 20, and 40 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The present study was conducted to establish a mass-rearing technique for improving the usability of Orius minutus (L.), an indigenous Asian species that is expected to show effective control in agriculture, because it is already adapted to domestic environments. Previous studies reported the potential of O. minutus as a biological control of aphids, leaf mites, and diamondback moths (Plutella xylostella (L.) (Lepidoptera: Plutellidae)) [13][14][15][16]. We also verified the predatory ability of the two-spotted spider mite (Tetranychus urticae Koch (Acari: Tetranychidae)), which was 1.39 times higher than that of O. laevigatus [17].…”
Section: Introductionsupporting
confidence: 69%
“…The present study was conducted to establish a mass-rearing technique for improving the usability of Orius minutus (L.), an indigenous Asian species that is expected to show effective control in agriculture, because it is already adapted to domestic environments. Previous studies reported the potential of O. minutus as a biological control of aphids, leaf mites, and diamondback moths (Plutella xylostella (L.) (Lepidoptera: Plutellidae)) [13][14][15][16]. We also verified the predatory ability of the two-spotted spider mite (Tetranychus urticae Koch (Acari: Tetranychidae)), which was 1.39 times higher than that of O. laevigatus [17].…”
Section: Introductionsupporting
confidence: 69%
“…There are many laboratory predation studies of Orius spp. on thrips, as well as some under field conditions in the Mediterranean basin and the Middle East . However, very little is known about Orius spp.…”
Section: Introductionmentioning
confidence: 99%
“…At all 4 temperatures, linear parameters (P 1 ) were negative (Table 1), showing that the functional responses were type II. A type II functional response has been found by many scientists with other insect species under various conditions (Bernal et al 1994; De Clercq Zamani et al 2006;Fathi & Nouri-Ganbalani 2009). Holling (1959 stated that invertebrates display a type II functional response whereas type III is found in vertebrate predators, but later this idea was rejected because parasitoids can also display a type III functional response.…”
Section: Discussionmentioning
confidence: 92%